دورالقيم السياسية في ترقية الحكم الراشد المشاركة السياسية ،الشفافية ،سيادة القانون في الجزائر نموذجا - قسوم, صلاح (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة إلى التعرف على منظومة من القيم ٬ وعلى العلاقة بين الحكم الراشد من خلال كل من عمليات الديمقراطية والتنمية . حيث العلاقة بين القيم والحكم الراشد تبادلية وتكاملية فلا غنى لأحدهما عن الآخر. وبعد استعراض كل التعاريف والخصائص المتعلقة بالقيم تبين أنها أداة للتغيير والتحول من نمط تقليدي إلى نمط الحداثة ولا يمكن إبعادها من الممارسة السياسية. فالحاجة إلى القيم في المجتمع كمثل الحاجة النفسية للإنسان ٬ حيث هذه الحاجات (القيم) تدفع الأفراد إلى التفاعل ضمن الجماعة وإخراج ميولهم واتجاهاتهم.فهيمصدر مهم لإشباع باقي الحاجات التي يحتاج إليها الفرد في حياته. وهو ما يعني اخضاع السلوك لأعراف معترف بها ومتفق عليها اجتماعيا شريطة قيامها على نظام متسق وغير متناقض.فيصبح التفاعل بين الأفراد منمنطق ٌأخلاقي. كما بينت نتائج الدراسة أن القيم السياسية بما فيها الحكم الراشد نفسه يتراجع تطبيقها في الساحة السياسية رغم ما بدل من جهود بسبب تراجع مؤشرات الديمقراطية والعدالة والشفافية وسيادة القانون والمساءلة واستشراء الفساد الذي لايقبل بالتعدد والمنافسة .غير أن ماهو كائن من قيم ومبادئ في إطارهذه الممارسة كفيل بالتغير والنهوض من جديد إذا أصر أفراد المجتمع على المطالبة بالمزيد من الانفتاح والحرية. Study Summary: The study aimed to identify a system of values and the relationship between good governance through both processes of democracy and development. Where the relationship between values and governance is mutual and complementary is not indispensable to each other. After reviewing all the definitions and characteristics of values, they were shown to be an instrument of change and transformation from a traditional to a modernist style and could not be excluded from political practice. The need for values in society is like the psychological need of people, where these needs (values) push individuals to interact within the group and to get out their tendencies and trends. It is an important source to satisfy the rest of the needs that the individual needs in his life. Which means subjecting behavior to socially recognized and agreed norms provided that they are based on a coherent and non-contradictory system. Interaction between individuals becomes a moral imperative. The results of the study also showed that political values, including high governance itself, are declining in the political arena, despite the efforts exerted by the decline of the indicators of democracy, justice, transparency, the rule of law, accountability and the spread of corruption, which does not tolerate pluralism and competition. However, And to rise again if community members insist on demanding greater openness and freedom.
أنظمة سياسية مقارنة و الحكم الراشد
Keywords: القيم ،السياسية ، المشاركة ، الشفافية; Values, politics, participation, transparency